Vitamin D3 concentration in serum of Diabetic Menopausal Women (Journal of the College of Basic Education, 2025)
Vitamin D is a fat soluble very important for regulation Calcium, Zinc and iron, menopausal women have deficiency estrogen level and that lead to increasing risk factor of reducing the density of bone, diabetes. Aim: To elevated the vitamin D3 concentration in diabetic menopausal women and compared with control group, and determine some clinical parameter. Method: this study consist of 70 women divided into two group (35 diabetic menopausal women and the other 35 was control group without diabetes mellitus), their age range 45-55 years old, collected from National Diabetic Center, Al-Mustansiriya University, Baghdad .Result: there was no significant appear in BMI and age of menopausal females with diabetic and control group, higher level of HbA1c and FBS in diabetic menopausal women with control group, while LH, FSH, and estrogen levels was significantly lower in diabetic menopausal women with control group. Vitamin D3concentration appeared significantly lower in diabetic menopausal women with control group. Conclusion: In diabetic menopausal women, vitamin D3 level was significant lower than control group.